Does Flypaper Effect Occurs On Local Government Expenditure? - Nur Fitriana Hamsyi; Fitriyani Fitriyani (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2021)
This research attempts to test whether the flypaper effect occurs in the relationship between original local government revenue and a balanced budget on local government expenditure in West Kalimantan Province. The data obtained were 14 regencies and cities in the period 2013-2019. Panel data is used in this study with analysis using Stata software. The result is that the flypaper effect phenomenon occurs in general allocation funds and special allocation funds for local government expenditure. This study also finds that general and special allocation funds positively affect local government expenditure, whereas the original local government revenue and sharing funds do not affect local government expenditure. It proves that local governments are still highly dependent on central government transfer funds rather than increasing their original local government revenue.